Strontium Chemistry with Silicone Grease - Harder, Sjoerd; Freitag, Benjamin; Stegner, Philipp; Pahl, Jürgen; Naglav, Dominik (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
Reaction of Sr(2-Me2N–Me3Si-benzyl)(2)(THF)(2) with one equivalent of DIPP(H)N-BH-N(H)DIPP (NBN-H-2, DIPP = 2,6-iPr-phenyl) gave the strontium bora-amidinate complex Sr(NBN)(THF)(4). Traces of silicone grease, however, can change the course of the reaction completely and gave the product Sr[(DIPP)NSiMe2O]THF(4) (1) in a ca. 25% yield. Complex 1 is a S-4 symmetric cluster with a Sr4O4 core and four chelating amide side arms. From the mother liquor a second product could be isolated: the dimeric cluster [Sr(NBN-SiMe2OSiMe2O)THF](2) (2). Whereas the synthesis of complex 2 is not reproducible, complex 1 can be prepared by deliberate addition of silicone grease. Also, it was found that Sr[N(SiMe3)(2)](2), 2,6-diisopropylphenyl and cyclic hexamethyltrisiloxane can be used as the reagents. For reactions with silicone grease, a mechanism, in which silicone precoordinates the central Sr atom followed by nucleophilic Si-O bond fission is proposed.
Keywords: Amides; Strontium; Silicone